The Development of Understanding Opacity in Preschoolers: A Transition From a Coarse- to Fine-Grained Understanding of Beliefs - Gut, Arkadiusz; Haman, Maciej; Gorbaniuk, Oleg; Chylińskia, Monika (Frontiers in Psychology, 2020)
Intensionality (or opacity) is a core property of mental representations and sometimes understanding opacity is claimed to be a part of children's theory of mind (evidenced with the false belief task). Children, however, pass the false belief task and the intensionality tasks at different ages (typically 4 vs. 5;1-6;11 years). According to two dominant interpretations, the two tests either require different conceptual resources or vary only in their executive or linguistic load. In two experiments, involving 120 children aged 3-6 (Experiment 1) and 75 children aged 4-6 (Experiment 2), we tested two variants of the executive load hypothesis: The differential linguistic complexity of the two tests, and the dual-name problem of the intensionality task. The former was addressed by standardizing and minimizing the linguistic demands of both tasks (contrasted with the typical narrative intensionality task), and the latter by introducing the dual-name problem into the false belief task as well, so that it was present in both tasks. We found that (1) two structurally different intensionality tasks shared more variance with each other than with the structurally similar false belief task, and that (2) introducing a dual label problem into the false belief task did not reduce the developmental gap. Our results speak against interpreting the difference between the time children pass the two tests entirely in terms of performative issues, and support the conceptual enrichment hypothesis. We discuss the theoretical relevance of these results, suggesting that they are best explained by fine-grained increments within the concept of belief, rather than a radical conceptual change. We conclude that understanding opacity of minds – which emerges between age 5 and 6 – is an important step towards a more advanced form of ToM.